THE EFFECT OF MOLASSES AS AN ADHESIVE MATERIAL FOR MAKING ENVIRONMENTALLY FRIENDLY LIVESTOCK PELLETS - wahyu fajar winata; Hafitz Noprianto Ramadhan; Dimas Betran Saputra (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2025)
This study aims to determine the effect of using molasses and starch adhesives on the physical quality of pellets made from fleshing waste generated by the leather tanning industry. The research employed a Completely Randomized Design (CRD) with three treatments: no adhesive (P0), addition of 2.5% molasses (P1), and addition of 2.5% starch (P2), each with three replications. The observed parameters included the physical characteristics of the pellets (color, texture, aroma, and compactness) as well as their reaction response to HCl solution. The results showed that the addition of adhesives significantly improved pellet quality. Treatment P1 produced the most compact, dense, and stable pellets, with a more intense reaction to HCl, while P2 provided moderate improvements and remained superior to P0. Pellets without adhesive (P0) had a loose structure, were less compact, and easily crumbled. Therefore, molasses is identified as the most effective adhesive for improving the physical quality and stability of pellets made from fleshing waste, whereas starch can serve as an alternative adhesive with lower effectiveness.